2023
DOI: 10.1021/acs.jmedchem.2c01992
|View full text |Cite
|
Sign up to set email alerts
|

Design of Sonosensitizers Integrated with Resveratrol Motif for Synergetic Sonodynamic Therapy and Nuclear Factor Kappa B Transcription Suppression of Breast Cancer

Abstract: Sonodynamic therapy (SDT) has been recognized as a spatial–temporal and noninvasive modality for the treatment of deep-seated tumors. However, current sonosensitizers suffer from low sonodynamic efficacy. Herein, we reported the design of nuclear factor kappa B (NF-κB) targeting sonosensitizers (TR1, TR2, and TR3) by integrating a resveratrol motif into a conjugated electron donor–acceptor (triphenylamine benzothiazole) skeleton. Among these sonosensitizers, TR2 with two resveratrol units in one molecule was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Chemical structures and optical properties of molecular sonosensitizers that are used in this study are shown in Figure . They are selected based on the existing literature including the most commonly studied one to the least studied one. They include chlorine e6, protoporphyrin IX, rose bengal, curcumin, IR780 iodide, emodin, doxorubicin, levofloxacin, tannic acid, epigallocatechin gallate (EGCG), and catechin. We have selected tannic acid, EGCG, and catechin due to their well-known therapeutic applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical structures and optical properties of molecular sonosensitizers that are used in this study are shown in Figure . They are selected based on the existing literature including the most commonly studied one to the least studied one. They include chlorine e6, protoporphyrin IX, rose bengal, curcumin, IR780 iodide, emodin, doxorubicin, levofloxacin, tannic acid, epigallocatechin gallate (EGCG), and catechin. We have selected tannic acid, EGCG, and catechin due to their well-known therapeutic applications.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound has a great potential for sonodynamic therapy with the wireless treatment option in a range of human diseases. This therapeutic approach requires sound-responsive materials, commonly known as sonosensitizers. Well-known sonosensitizers include microbubbles, piezoelectric nanoparticles, and some selected organic small molecules. Among them, microbubbles are the most popular due to their high sound-responsive property, although their large size restricts the in vitro / in vivo targeting options. Similarly, piezoelectric nanoparticles are promising, although their design with high sound-responsive performance is challenging. In contrast, organic small molecule-based sonosensitizers are attractive due to their clear chemical structure and smaller size. However, they must have specific functional groups to offer the sonodynamic activity, and a clear understanding of the origin of such activity is yet to be established . Moreover, small molecule sonosensitizers are hydrophobic/organic in nature with low water solubility and low cell/tumor specificity and have a short circulation time in physiological conditions …”
Section: Introductionmentioning
confidence: 99%